Criminal law: concepts, crimes, and defenses - Corn, Geoffrey S. (Carolina Academic Press, 2023)
"This book offers a comprehensive survey of the major concepts and doctrines in criminal law, describing both the common law and the Model Penal Code approaches to each issue"--